Osteoclast Deficiency Results in Disorganized Matrix, Reduced Mineralization, and Abnormal Osteoblast Behavior in Developing Bone - Dai, Xu‐Ming; Zong, Xiao‐Hua; Akhter, Mohammed P; Stanley, E Richard (Journal of bone and mineral research, 2004)
Studies of the influence of the osteoclast on bone development, in particular on mineralization and the formation of the highly organized lamellar architecture of cortical bone by osteoblasts, have not been reported. We therefore examined the micro‐ and ultrastructure of the developing bones of osteoclast‐deficient CSF‐1R‐nullizygous mice (Csf1r−/− mice). Introduction: Colony‐stimulating factor‐1 receptor (CSF‐1R)‐mediated signaling is critical for osteoclastogenesis. Consequently, the primary defect in osteopetrotic Csf1r−/− mice is severe osteoclast deficiency. Csf1r−/− mice therefore represent an ideal model system in which to investigate regulation by the osteoclast of osteoblast‐mediated bone formation during development. Materials and Methods: Bones of developing Csf1r−/− mice and their littermate controls were subjected to X‐ray analysis, histological examination by light microscopy and transmission electron microscopy, and a three‐point bending assay to test their biomechanical strength. Bone mineralization in embryonic and postnatal bones was visualized by double staining with alcian blue and alizarin red. Bone formation by osteoblasts in these mice was also examined by double‐calcein labeling and in femoral anlagen transplantation experiments. Results and Conclusions: Frequent spontaneous fractures and decreased strength parameters (ultimate load, yield load, and stiffness) in a three‐point bending assay showed the biomechanical weakness of long bones in Csf1r−/− mice. Histologically, these bones have an expanded epiphyseal chondrocyte region, a poorly formed cortex with disorganized collagen fibrils, and a severely disturbed matrix structure. The mineralization of their bone matrix at secondary sites of ossification is significantly reduced. While individual osteoblasts in Csf1r−/− mice have preserved their typical ultrastructure and matrix depositing activity, the layered organization of osteoblasts on the bone‐forming surface and the direction of their matrix deposition toward the bone surface have been lost, resulting in their abnormal entrapment by matrix. Moreover, we also found that (1) osteoblasts do not express CSF‐1R, (2) the bone defects in Csf1r−/− embryos develop later than the development of osteoclasts in normal embryos, and (3) the transplanted Csf1r−/− femoral anlagen develop normally in the presence of wildtype osteoclasts. These results suggest that the dramatic bone defects in Csf1r−/− mice are caused by a deficiency of the osteoclast‐mediated regulation of osteoblasts and that the osteoclast plays an important role in regulating osteoblastic bone formation during development, in particular, in the formation of lamellar bone.